Effects of the atrium on intraventricular flow patterns during mechanical circulatory support. Issue 4 (April 2022) - Ghodrati, Mojgan; Schlöglhofer, Thomas; Maurer, Alexander; Khienwad, Thananya; Zimpfer, Daniel; Beitzke, Dietrich; Zonta, Francesco; Moscato, Francesco; Schima, Heinrich; Aigner, Philipp
Simulations of the ventricular flow patterns during left ventricular assist device (LVAD) support are mainly performed with idealized cylindrical inflow, neglecting the influence of the atrial vortex. In this study, the influence of the left atrium (LA) on the intra-ventricular flow was investigated via Computational Fluid Dynamics (CFD) simulations. Ventricular flow was simulated by a combined Eulerian (carrier flow)/Lagrangian (particles) approach taking into account either the LA or a cylindrical inflow section to mimic a fully support condition. The flow deviation at the mitral valve, the blood low-velocity volume as well as the residence time and shear stress history of the particles were calculated. Inclusion of the LA deflects the flow at the mitral valve by 25°, resulting in an asymmetric flow jet entering the left ventricle. This reduced the ventricular low-velocity volume by 40% (from 6.4 to 3.9 cm 3 ), increased (40%) the shear stress experienced by particles and correspondingly increased (27%) their residence time. Under the studied conditions, the atrial geometry plays a major role in the development of intraventricular flow patterns. A reliable prediction of blood flow dynamics and consequently thrombosis risk analysis within the ventricle requires the consideration of the LA in computational simulations.